Prognostic Importance of Hyponatremia in Acute STEMI (Academia Journal of Medicine, 2020)
Background: Hyponatremia develops in early phases of acute myocardial infarction, recently, several studies showing its importance as  important early prognostic tool. Many studies shown that significant increase in plasma AVP level was in patients who had associated with  complication as heart failure and fatal outcome after acute MI, and clinical improvement was noted following the rise in serum plasma level of  sodium. hence Early developed hyponatremia is a unique indicator of neuro hormonal activity in the early phases of recent MI, so it can help  predict the complication as long-term development of HF and death. OBJECTIVE: To observe the prognostic importance of hyponatremia in  settings of acute STEMI event and helpfulness in prediction of short term and long term survival. Subjects and Methods: Randomized double blinded study, in 100 of patients with acute S TEMI presented to outpatient department and indoor emergency patients. Results: Patients who  developed hyponatremia at admission had higher mortality rate than the patients who developed hyponatremia at 72 hrs and normonatremic  patients. Mortality in patients correlates with the severity of hyponatremia 5(100%) patient died with sodium levels
Keywords: Hyponatremia; STEMI; Prognosis; Heart Failure